Extremely rare skin and soft tissue infection caused by Mycobacterium wolinskyi - Takahiko Fukuchi (Journal of Global Antimicrobial Resistance)
AIM: To describe extremely rare pathogen in humans. BACKGROUND: Cases of non-tuberculous mycobacterium infection are increasing in developed countries, despite a decline in tuberculosis prevalence. We experienced a Mycobacterium(M.) wolinskyi infection resulting in bilateral axillary lymphadenopathy after surgery for urological malignancy. METHODS: A 74-year-old Japanese man was referred to our department. He had undergone surgery for prostate cancer four months earlier, and 1.5 months after surgery he noticed erythema around the camera port, one week later the pain spread to the left axilla, and two weeks later to the bilateral axillary lymph node and the left mammary gland. Positron Emission Tomography-Computed Tomography revealed accumulation in the bilateral lung fields, bilateral axillae and left anterior thoracic and umbilical regions. A biopsy of the left breast revealed no evidence of malignancy, but granulomatous changes which led him to the infectious disease department. M. wolinskyi was cultured from the right axillary lymph node biopsy specimen. According to the susceptibility results, the patient was treated with levofloxacin, sulfamethoxazole/trimethoprim and doxycycline for three months, without any recurrence. RESULTS: M. wolinskyi infection has only been reported in about 30 human cases to date, with reports of surgical site infection, peritonitis, bacteremia, infective endocarditis and prosthetic joint infections, as well as skin and soft tissue infections. The patients’ background included immunocompromised patients such as umbilical cord blood transplant recipient, chronic myelogenous leukemia and end-stage kidney disease, but the majority were more immunocompetent patients. CONCLUSION: We need to accumulate experience with this rare pathogen.